Pragmatic Analysis of Flouting Maxim in Donald Trump’s Interview with TIME in the Oval Office 2020 - Latifatun Nuzulia, Isma Farikha (Journal of English Language Teaching and Linguistics, 2020)
The purpose of this research is to define a linguistic feature based on Donald Trump’s interview with TIME since Trump is a politician who has the power to influence others, and it can be extremely essential to analyze how the hidden meaning in his utterance images him as a public figure. This research uses the descriptive qualitative method because the object of the study is a transcript containing utterance and conversation. Grice's (1975) theory is used in this study to define the flouting maxim that occurs  during the interview. The result of this study is that 11 utterances containing flouting maxim of quantity, 3 flouting the maxim of relation, 2 flouting the maxim of manner, and no flouting maxim of quality is found in this study. After analyzing the finding, the most dominant found types is flouting maxim of quantity which means that Trump frequently gives more information than required to express his interest and to show his power as a president and his nationalism as representative of American.